Histomorphometric and Histopathological Alterations of Rat Testis Following Exposure to Hydrogen ‎Peroxide: Protective Role of Resveratrol Supplement - Abdulla, Jasim M; Al-Okaily, Baraa N (The Iraqi Journal of Veterinary Medicine, 2022)
Resveratrol (RS) is widely used in medical fields as an antioxidant. Current research investigated ‎the protective role of RS supplement on histomorphometric and histopathological alterations in ‎testes were caused by hydrogen peroxide (H2O2) of rats as an animal model. Thirty-two adult ‎rats were utilized in this study, divided randomly into 4 equal groups as follows. The group C ‎was given tap water only and served as control, the 2nd group (G1) was given 0.5% of H2O2 of ‎tap water, the 3rd group (G2) was given tap water containing 0.5% of H2O2 and intubated RS ‎supplement at 87 mg/kg BW, and 4th group intubated RS supplement 87 mg/kg BW. after 56 ‎days of treatment, rats were euthanized, dissected then, specimens of testes tissue were collected ‎for histomorphometric and histopathological evaluation. Our results showed that administration ‎of H2O2 caused a significant histomorphometric with histopathological changes in the form of a ‎thickness of fibrous tunica albuginea, disarrangement of germ cells, necrosis of spermatogonia, ‎edema, and loss of sperms as compared to other groups. Meanwhile, these histological alterations ‎were partially attenuated in the G2 group that intubated resveratrol. Thus, the current study ‎concluded that resveratrol may have therapeutic value in the treatment of induced testicular injury ‎by H2O2 due to its antioxidant activity and attenuation of harmful effects of oxidative ‎stress through a mechanism that should be elucidated in future studies.